Analisis Produk Unggulan Daerah Di Kabupaten Jepara - A Khoirul Anam; Elly Widiastuti; Aji Nugroho; Anik Suharwati; Amalia Rachma Fatchiyyah (Jurnal Dinamika Ekonomi & Bisnis, 2022)
This study aims to analyze and map local superior commodities (LSC) in Jepara Regency using Shift Share Analysis, Growth Ratio Model Analysis (MRP), Location Quotient (LQ) Analysis, Overlay Analysis, and Klassen Typology Analysis. The analysis was carried out using the GRDP data for Jepara Regency and for Central Java Province. The research was conducted on five business sectors including the creative industry sector, the food processing sector, the food crop & plantation product processing sector, the fishery product processing sector and the agricultural product processing sector. The results of the identification of superior commodities in Jepara Regency show that the manufacturing sector has strong competitiveness or has a highly competitive advantage. It implies that local governments need to pay attention to business sectors that are experiencing a decline and relatively underdeveloped, improve managerial capabilities for business actors, especially in the manufacturing industry sector, and increase market access offline and online (omni), as well as develop innovation hubs.